Peran Ekstrak Anggur Laut terhadap Penurunan Kadar Kolesterol LDL Rattus norvegicus Jantan yang Mendapat Diet Tinggi Lemak - RONALDO LAU; SULISTIANA PRABOWO; RIAMI (Universitas Hang Tuah, 2020)
Abstract Background: High fat diet increase the absorption of lipid in the intestinum, that can lead to increase LDL cholesterol level in the blood. Sea grapes extract (Caulerpa racemosa) contains antioxidant polyphenolic group that can reduce MTP and ACAT-2 in the body that can decrease LDL cholesterol level in the blood.The purpose of this study is to know the effect of sea grapes extract on decreasing LDL cholesterol of white male Wistar rats (Rattus norvegicus) fed with high fat diet. Method: 24 white male Wistar rats, that divided into 3 groups: 1) group of rats fed with standard diet for 28 days; 2) group of rats fed with high fat diet for 28 days; 3) group of rats fed with high fat diet for 28 days and given 10 gram/kg body weight/day of sea grapes extract on 15th-28th days. Then the blood LDL cholesterol level measured on the 29th day. Result : One-Way ANOVA Test showed there was significant difference (p=0.004) of LDL level between the group of rats fed with standard diet (12.37 mg/dl) compared to group of rats fed with high fat diet (17.87 mg/dl). There was significant difference (p=0.001) of LDL level between the group of rats fed with high fat diet (17.87 mg/dl) compared to group of rats fed with high fat diet and sea grapes extract (10.12 mg/dl). Conclusion: high fat diet significantly increase blood LDL cholesterol level and sea grapes extract (Caulerpa racemosa) significantly decrease blood LDL cholesterol level